Investigating the state of renewable energy and concept of pump as turbine for energy generation development. (November 2020) - Adu, Daniel; Jianguo, Du; Darko, Ransford O.; Boamah, Kofi Baah; A.-Boateng, Emmanuel
Abstract: Access to consistent and clean energy is a key challenge faced by several countries globally; especially in Asian and African countries. Most of the communities within these and other regions in the world are faced with continuous energy crisis, causing most of these economies to cripple. It is estimated that billions of people worldwide are living without access to clean and reliable source of energy. Renewable energy is the biggest source of energy and it characterizes the basis to steer the energy system in the direction of sustainability and supply security. Several countries globally are blessed with rich renewable energy resources that have not been fully developed. These renewable resources have the potentials to change the status quo of power generation and consumption in these countries. In this study, the status of renewable energy generation and storage was identified and discussed. A specific centrifugal pump model with radial volute and 6 impeller blades having inlet and outlet diameter of 104 mm and 160 mm respectively. The operational parameter of the head is 16 m, flow rate is 12.5 m3/h, rotational speed is 2900 r/min and efficiency is 56% were selected to carry out numerical simulations in the study. Using the centrifugal pump to operate as turbine (PAT), is one of the best alternatives for small and micro hydro generation since it helps in meeting energy needs. Furthermore, it can also help improve economic growth due to its cheapest source of power generation as well as providing sustainable energy source that will create more employment opportunities to improve the socio-economic environments of the people. Moreover, PAT method are also advantageous because of its low cost in acquisition and maintenance. The characteristics of PAT have been discussed numerically to analyze pressure and velocity distribution at different rotational speeds. The study concludes that PAT is the best alternative for energy generation.